Stereotip Melayu Malas dan Pengaruhnya pada Etos Kerja - Novalita Sandy; Puspitawati Puspitawati (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to determine the stereotype Melayu Malas on Ethnic Malay associated with the term "kojo saibu tak kojo mangatus kojo tak kojo saibu mangatus" for the effect on the work ethic, and community perceptions of the negative stigma on Ethnic Malays, as well as the impact of stereotypes. This research is a qualitative descriptive study, using data collection techniques with non participation observation and interviews, the researchers not directly involved with community activities but only observe and conduct a question and answer. Based on the research method is the verdict that stereotype Malay lazy aimed at the Malay community in the Village Nenassiam is the result of past experiences of ethnic groups that serve as self image to the Malays that gives effect to the work ethic masyarakatanya, where it has become the benchmark for welfare is considered to have a relaxed work ethic and want delish without life planning ahead so that the results obtained are also modest. The views of the public like two sides of a coin, on one hand the people refused regarded as Malays lazy but the other communities is also confirmed that the Malays are lazy, while the impact of stereotypes Malay lazy affects three things: social relations, ethnic conflicts, identity ethnicity.